The INTERNET STUDY: A phase II study of everolimus in patients with fluorodeoxyglucose (18F) positron‐emission tomography positive intermediate grade pancreatic neuroendocrine tumors. Issue 3 (7th February 2020) - Lung, Mei Sim; Hicks, Rodney J.; Pavlakis, Nick; Link, Emma; Jefford, Michael; Thomson, Benjamin; Wyld, David K.; Liauw, Winston; Akhurst, Timothy; Kuru, Narmatha; Michael, Michael
Abstract: Aims: This multicenter phase II trial evaluates the efficacy of everolimus in poor prognosis grade 2 (G2) pancreatic neuroendocrine tumors (PNETs), defined by 2‐[fluorine‐18]fluoro‐2‐deoxy‐d‐glucose (FDG) positron‐emission tomography (PET) avidity. FDG–PET avidity in NETs is associated with a significantly higher risk of death, outperforming Ki‐67 index or liver metastases as a poor prognostic factor. We hypothesized that everolimus has efficacy in patients with FDG–PET‐avid G2 PNETs and prospectively evaluated progression‐free survival (PFS) and response in the first‐line setting. Methods: Patients with FDG–PET‐avid G2 advanced PNET received everolimus 10 mg daily until disease progression. Patients were staged every 12 weeks with CT/MRI and FDG–PET and every 24 weeks with Gallium 68 (68Ga) 1, 4, 7, 10‐tetraazacyclododecane‐1, 4, 7, 10‐tetraacetic acid (DOTA)–octreotate (DOTATATE, GaTate) PET. The primary endpoint was PFS at 6 months. Overall survival rate, PET/structural imaging response and toxicity were also measured. Results: Nine patients were accrued from December 2012 to February 2015. Median treatment duration was 13.8 months. The estimated PFS rate at 6 months was 78%. The best response on CT/MRI was stable disease in nine patients (100%) and partial response on FDG–PET in five patients (55.5%). Treatment‐related adverse effects were consistent with previous studies of everolimus. Conclusion: Everolimus is active with prolonged disease control in poor prognosis FDG‐avid G2 PNETs. Treatment individualization based on functional imaging warrants further evaluation.